Answer:
[tex]y=13(4)^x[/tex]
Step-by-step explanation:
We have the exponential function of the form:
[tex]y=ab^x[/tex]
And it goes through the points (0, 13) and (3, 832).
Hence, when we substitute in 0 for x, we should get 13 for y. Therefore:
[tex]13=ab^0[/tex]
Since anything to the zeroth power is 1, this yields:
[tex]a=13[/tex]
So, we determined that the value of a is 13.
So, our function is now:
[tex]y=13b^x[/tex]
We will need to determine b. We know that y equals 832 when x is 3. Hence:
[tex]832=13(b)^3[/tex]
Divide both sides by 13:
[tex]b^3=64[/tex]
Take the cube root of both sides:
[tex]b=4[/tex]
Hence, our b value is 4.
Therefore, our entire equation is:
[tex]y=13(4)^x[/tex]